Field-emission source of chages based on nanotubes for low temperature experiments - Borisenko, D.N.; Walmsley, P.M.; Golov, A.I.; Kolesnikov, N.N.; Kotov, Yu.V.; Levchenko, A.A.; Fear, M.J. (Recent Contributions to Physics, 2015)
In this report we present two methods of production of field-emission charge sources based on carbon nanotubes, that can be used in low-temperature investigation of properties of injected charges in cryogenic liquids and crystals. The sources were made from metal disks with a diameter of 10 mm and thickness of about 1 mm. The thermal emission on a source does not exceed E<10-6 W.